Michele Serros merchandise price list
A price List for Michele Serros book Chicana Role Model $15, Chicana Falsa $20, Honey Blonde Chica $15, and t-shirts. T-Shirts selling price Brown T-shirts $20 and baby brown T's $15. Date not provided.